High modulus glass fiber composition with reduced energy consumption

Through the design of specific glass compositions, the problems of high energy consumption and greenhouse gas emissions in glass fiber manufacturing are solved, and glass fiber production with high elastic modulus and low CO2 emissions are achieved under low energy conditions, which improves mechanical performance and equipment life.

CN119137079APending Publication Date: 2024-12-13OWENS CORNING INTELLECTUAL CAPITAL LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380035830.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-18
Filing Date
2023-04-17
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the existing glass fiber manufacturing process, the high energy consumption of molten raw materials and greenhouse gas emissions are difficult to simultaneously reduce the melting temperature and CO2 emissions of glass fibers while maintaining high elastic modulus and mechanical characteristics.

Method used

Using a specific glass composition, the content of SiO2 in the range of 50-58%, Al2O3 in 18-23%, a small amount of CaO and MgO, at least 5% Y2O3 and La2O3, the ratio of Y2O3/La2O3 is between 2-4, Li2O, Na2O and The glass composition of K2O forms glass fibers with low fiber forming temperature and high sound fiber elastic modulus by adjusting the SiO2/(MgO+CaO) ratio and the liquid phase line temperature.

Benefits of technology

The production of glass fibers with high elastic modulus and low CO2 emissions under low energy conditions has been achieved, which extends the equipment life, reduces manufacturing costs, and improves the mechanical properties of glass fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005097835490000151
    Figure BDA0005097835490000151
  • Figure BDA0005097835490000162
    Figure BDA0005097835490000162
  • Figure BDA0005097835490000163
    Figure BDA0005097835490000163
Patent Text Reader

Abstract

The invention discloses a glass composition. The glass composition comprises SiO2 in an amount of from 50 wt% to 58 wt%; al2O3 in an amount of from 18 wt% to 23 wt%; less than 18% by weight of CaO and MgO; at least 5% by weight of Y2O3 and La2O3, wherein Y2O3 and La2O3 are present in a ratio (R1 = Y2O3 / La2O3) of between 2 and 4. Glass fibers formed from the glass composition have an acoustic fiber elastic modulus of at least 94.5 GPa.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] Glass fibers are made from various raw materials combined in specific proportions to produce a desired composition, generally referred to as "glass batch." This glass batch can be melted in a melting device, and the molten glass is drawn into glass filaments through a bushing or orifice plate (the resulting glass filaments are also referred to as continuous glass fibers).

[0002] As the glass manufacturing industry moves toward more environmentally friendly and sustainable manufacturing processes, one major aspect focuses on reducing the energy required to melt the glass raw materials used to make glass fiber. Lowering the temperature required to melt the raw materials will generally reduce the amount of energy consumed in the manufacturing process and may also help extend the life of the melting and bushing equipment. By reducing the amount of energy consumed, the carbon footprint is ultimately reduced as well.

[0003] In addition, melting conventional raw materials usually results in the release of certain gases such as greenhouse gases (GHGs) into the atmosphere. For example, large amounts of carbonate-based raw materials such as limestone and dolomite are often used to facilitate the processing of materials and to impart desired properties to glass products. However, the melting of such carbonate-based raw materials can result in the generation of GHGs, such as carbon dioxide. The generation of GHGs can also be caused by other methods commonly used in conventional glass fiber manufacturing processes, such as by the combustion reactions involved in power generation that provide energy for melting raw materials, and also during fiber forming of molten glass.

[0004] Therefore, as sustainable and environmentally friendly solutions are at the forefront of manufacturing initiatives, there is a need for glass fiber compositions that have reduced melting temperatures and emit less GHGs into the atmosphere during the glass fiber manufacturing process while maintaining desired mechanical properties, such as high elastic modulus and tensile strength. Summary of the invention

[0005] Various exemplary aspects of the present inventive concepts relate to a glass composition comprising: SiO2 in an amount of 50 wt% to 58 wt%; Al2O3 in an amount of 18 wt% to 23 wt%; CaO and MgO in an amount of less than 18 wt%; at least 5 wt% of Y2O3 and La2O3, wherein Y2O3 and La2O3 are present in a ratio R1 between 2 and 4 (R1=Y2O3 / La2O3); Li2O in an amount of 1 wt% (or greater than 1 wt%) to 2 wt%; Na2O in an amount of 0 wt% to 0.1 wt%; K2O in an amount of 0 wt% to 0.2 wt%; TiO2 in an amount of 0 wt% to 0.5 wt%. In any exemplary embodiment, the glass composition may have a ratio R2 (R2 = SiO2 / (MgO+CaO)) between 3.1 and 3.75, a glass fiber forming temperature of less than 1,300° C., a liquidus temperature of no greater than 1,250° C., and / or a ΔT of at least 10° C. Glass fibers formed from the glass composition have a sonic fiber elastic modulus of at least 94.5 GPa.

[0006] Another exemplary aspect of the present inventive concept relates to a glass fiber formed from a glass composition, the glass composition comprising: SiO2 in an amount of 50 wt% to 56 wt%; Al2O3 in an amount of 18 wt% to 23 wt%; CaO and MgO in an amount of less than 18 wt%; Y2O3 in an amount of 4.5 wt% to 8 wt%; La2O3 in an amount of 0.5 wt% to 4 wt%; wherein Y2O3 and La2O3 are present in a ratio R1 between 2 and 4 (R1=Y2O3 / La2O3); Na2O+K2O in an amount of 0 wt% to 0.5 wt%; and TiO2 in an amount of 0 wt% to 0.5 wt%. In any exemplary embodiment, the glass composition may have a ratio R2 (R2=SiO2 / (MgO+CaO)) between 3.1 and 3.75. The glass fibers may have a density between 2.55 g / cc and 2.8 g / cc and / or an acoustic fiber elastic modulus of at least 94.5 GPa.

[0007] Another exemplary aspect of the inventive concept relates to a reinforced composite product comprising a polymer matrix and a plurality of glass fibers formed from a glass composition. The glass composition comprises SiO2 in an amount of 50 wt% to 58 wt%; Al2O3 in an amount of 18 wt% to 23.0 wt%; CaO and MgO less than 18 wt%; at least 5 wt% Y2O3 and La2O3, wherein Y2O3 and La2O3 are present in a ratio R1 between 2 and 4 (R1=Y2O3 / La2O3); Li2O in an amount greater than 1 wt% to 2 wt%; Na2O in an amount of 0 wt% to 0.1 wt%; K2O in an amount of 0 wt% to 0.2 wt%; TiO2 in an amount of 0 wt% to 0.5 wt%, wherein the glass composition has a ratio R2 (R2=SiO2 / (MgO+CaO)) between 3.1 and 3.75. The glass composition may have a liquidus temperature of no greater than 1,250° C. and a ΔT between 10° C. and 60° C. A glass fiber formed from the glass composition may have a sonic fiber elastic modulus of at least 94.5 GPa.

[0008] Another exemplary aspect of the present inventive concept is directed to a glass composition comprising: SiO2 in an amount of 50 wt% to 58.0 wt%; Al2O3 in an amount of 18 wt% to 23 wt%; CaO and MgO in an amount of less than 18 wt%; and at least 5 wt% Y2O3 and La2O3, wherein Y2O3 and La2O3 are present in a ratio (R1=Y2O3 / La2O3) between 2 and 4. The glass composition has a fiber forming temperature between 1,200°C and 1,300°C and a ΔT of at least 10°C, and wherein a glass fiber formed from the glass composition may have an acoustic fiber elastic modulus of at least 94.5 GPa.

[0009] The foregoing and other objects, features and advantages of the present invention will become more fully apparent upon consideration of the following detailed description. DETAILED DESCRIPTION

[0010] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those of ordinary skill in the art to which these exemplary embodiments belong. The terms used in the description herein are only used to describe the exemplary embodiments and are not intended to limit the exemplary embodiments. Therefore, the overall inventive concept is not intended to be limited to the specific embodiments shown herein. Although other methods and materials similar or equivalent to those described herein can be used in the implementation or testing of the present invention, preferred methods and materials are described herein.

[0011] As used in the specification and the appended claims, the singular forms "a", "an" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.

[0012] Unless otherwise indicated, all numbers used in the specification and claims expressing the amounts of ingredients, chemical and molecular properties, reaction conditions, etc. should be understood as being modified in all cases by the term "about". Therefore, unless otherwise indicated, the numerical parameters set forth in the specification and the appended claims are approximate values ​​that may vary depending on the desired properties sought to be obtained by the exemplary embodiments herein. At least each numerical parameter should be interpreted in light of the number of significant figures and ordinary rounding techniques.

[0013] Although the numerical ranges and parameters of the wide range of exemplary embodiments are approximate values, the numerical values ​​described in the specific examples are reported as accurately as possible. However, any numerical value inherently contains certain errors inevitably caused by the standard deviation present in their respective test measurements. Each numerical range given throughout the specification and claims will include each narrower numerical range that falls within such a wider numerical range, as if such a narrower numerical range is clearly written out in this article. In addition, any numerical value reported in the examples can be used to define the upper or lower endpoints of the wider composition range disclosed herein.

[0014] While the glass compositions of the subject inventive concepts may be described and / or claimed in various ways, it should be understood that the different compositions are alternative solutions to the specific problems addressed herein and are an integral part of the disclosed general inventive concepts.

[0015] The present disclosure relates to a glass composition having a specially tailored composition to provide glass fibers having a high elastic modulus, a low density, and an improved temperature profile, such that the glass requires less energy to melt during manufacture and emits less greenhouse gases, particularly carbon dioxide. Such glass compositions are particularly beneficial in the field of wind energy products, such as wind turbines that require longer blades in order to generate more energy. Longer blades require materials with a higher elastic modulus in order to withstand the forces applied to them without breaking. In fact, the elastic modulus of the glass fiber has a large impact on the final product properties, because even a small improvement in the glass fiber modulus multiplied by the total fiber weight fraction of the composite product will result in a large improvement overall.

[0016] The glass compositions disclosed herein are suitable for melting in conventional, commercially available refractory-lined glass melting furnaces, which are widely used in the manufacture of glass reinforcement fibers.

[0017] The glass composition may be in a molten form, obtainable by melting the components of the glass composition in a melter. The glass composition exhibits a low fiber forming temperature, which is defined as a temperature corresponding to a melt viscosity of about 1000 poise, as determined by ASTM C965-96 (2007). Lowering the fiber forming temperature can reduce the production cost of the glass fibers because it allows for longer bushing life and reduced energy usage necessary to melt the components of the glass composition. Thus, the energy expended is generally less than that required to melt many commercially available glass formulations, including Such lower energy requirements can also reduce the overall manufacturing costs associated with the glass composition.

[0018] In some exemplary embodiments, the glass composition has a fiber forming temperature of less than 2,372°F (1,300°C), including no greater than 2,354°F (1,290°C), no greater than 2,327°F (1,275°C), no greater than 2,309°F (1,265°C), no greater than 2,291°F (1,255°C), no greater than 2,282°F (1,250°C), no greater than 2,273°F (1,245°C), and no greater than 2,264°F (1,240°C). In any exemplary embodiment, the glass composition may have a temperature between 2,192°F (1,200°C) and 2,372°F (1,300°C), including between 2,228°F (1,210°C) and 2,300°F (1,260°C), and between 2,246°F (1,230°C) and 2,264°F (1,240°C), including all endpoints and subranges therebetween.

[0019] Another fiber forming characteristic of glass composition is liquidus temperature.Liquidus temperature is defined as the highest temperature when there is equilibrium between liquid glass and its main crystalline phase.In some cases, liquidus temperature (ASTM C829-81 (2005)) can be measured by exposing the glass composition to the temperature gradient in the platinum alloy boat and continuing for 16 hours.At all temperatures above the liquidus temperature, the glass is completely melted, that is, it does not contain crystals.At a temperature below the liquidus temperature, crystals can be formed.It is desirable to have the lowest possible liquidus temperature in order to form a processing window (referred to as ΔT, defined in more detail below).Low liquidus temperature also helps to reduce crystal formation in the coldest position of the melting device, and improves the processability of the glass.

[0020] In some exemplary embodiments, the glass composition has a liquidus temperature less than 2,282°F (1,250°C), including a liquidus temperature no greater than 2,264°F (1,240°C), no greater than 2,246°F (1,230°C), no greater than 2,237°F (1,225°C), no greater than 2,219°F (1,215°C), no greater than 2,210°F (1,210°C), no greater than 2,201°F (1,205°C), no greater than 2,192°F (1,200°C), and no greater than 2,183°F (1,195°C). In any exemplary embodiment, the glass composition may have a liquidus temperature between 2,102°F (1,150°C) and 2,282°F (1,250°C), including between 2,147°F (1,175°C) and 2,255°F (1,235°C), and between 2,192°F (1,180°C) and 2,192°F (1,200°C).

[0021] The third fiber forming property is "ΔT", which is defined as the difference between the fiber forming temperature and the liquidus temperature. In view of the low forming temperature, the ΔT of the glass composition must be greater than 0 and is specifically selected to provide a glass composition with a sufficient forming window. In any exemplary embodiment, the glass composition has a ΔT of at least 3°C, including at least 10°C, at least 15°C, at least 20°C, at least 24°C, at least 27°F, at least 30°C, at least 33°C, and at least 35°C. In various exemplary embodiments, the glass composition has a ΔT between 3°C and 80°C, including between 12°C and 80°C, between 15°C and 60°C, between 20°C and 55°C, between 25°C and 50°C, and between 30°C and 45°C.

[0022] In order to obtain a glass composition capable of producing a high modulus glass with reduced CO2 emissions, the glass composition generally contains reduced concentrations of CaO and MgO. However, in general, it is generally known that increasing the calcium and magnesium content is an effective way to reduce temperatures, especially fiber forming temperatures. However, it has been surprisingly discovered that by incorporating at least 5.0 wt. % of a synergistic blend of rare earth oxides Y2O3 and La2O3, the total concentration of CaO and MgO can be reduced while still obtaining a glass composition with a low fiber forming temperature capable of forming glass fibers having an acoustic fiber elastic modulus of at least GPa.

[0023] It has been found that this specific combination and concentration of rare earth oxides Y2O3 and La2O3 helps to reduce the fiber forming temperature while allowing the produced glass fiber to have sufficient elastic modulus and tensile strength. Therefore, in any exemplary embodiment, the glass composition contains Y2O3 and La2O3. Specifically, the main glass composition contains a total concentration of Y2O3 and La2O3 of at least 5 weight%, wherein the ratio (R1) of Y2O3 / La2O3 is between 2 and 4. In any exemplary embodiment, the glass composition includes a Y2O3 / La2O3 ratio (R1) between 2.2 and 3.8, including between 2.4 and 3.6, between 2.6 and 3.4, between 2.8 and 3.2, and between 2.9 and 3.1, including all endpoints and sub-ranges therebetween. In addition, as described above, the total concentration of Y2O3 and La2O3 is at least 5 wt%, including, for example, at least 5.5 wt%, at least 5.7 wt%, at least 6 wt%, at least 6.3 wt%, at least 6.5 wt%, at least 6.8 wt%, at least 7 wt%, at least 7.2 wt%, and at least 7.5 wt%. Similarly, the total concentration of Y2O3 and La2O3 may be no greater than 15 wt%, including, for example, no greater than 9.6 wt%, no greater than 9.4 wt%, no greater than 9.2 wt%, no greater than 9 wt%, no greater than 8.8 wt%, no greater than 8.4 wt%, and no greater than 8 wt%. In any exemplary embodiment, the glass composition may contain Y2O3 and La2O3 in an amount greater than 5 wt% and less than 10 wt% overall, including between 5.5 wt% and 9.8 wt%, between 5.8 wt% and 9.5 wt%, between 6.0 wt% and 9.2 wt%, between 6.3 wt% and 9 wt%, between 6.5 wt% and 8.8 wt%, between 7 wt% and 8.5 wt%, and between 7.2 wt% and 8.2 wt%, including all endpoints and ranges therebetween.

[0024] Individually, the glass composition may include at least 4 wt % Y2O3, including, for example, at least 4.2 wt %, 4.4 wt %, 4.6 wt %, at least 4.8 wt %, at least 5 wt %, at least 5.2 wt %, at least 5.5 wt %, at least 5.4 wt %, at least 5.6 wt %, and at least 5.8 wt % relative to these oxides. Likewise, the glass composition may include no greater than 8 wt % Y2O3, including, for example, no greater than 7.8 wt %, no greater than 7.5 wt %, no greater than 7.3 wt %, no greater than 7 wt %, no greater than 6.8 wt %, no greater than 6.5 wt %, and no greater than 6.3 wt % Y2O3. In any exemplary embodiment, the glass composition may include greater than 5 wt % to less than 8 wt %, including between 5.4 wt % and 7.5 wt %, between 5.6 wt % and 7 wt %, and between 5.8 wt % and 6.7 wt %, including all endpoints and ranges therebetween.

[0025] In addition, the glass composition may include at least 0.5 wt%, including, for example, at least 0.75 wt%, 0.9 wt%, 1 wt%, at least 1.3 wt%, at least 1.5 wt%, at least 1.7 wt%, at least 1.9 wt%, and at least 2 wt% La2O3. Likewise, the glass composition may include no more than 4 wt% La2O3, including, for example, no more than 3.8 wt%, no more than 3.5 wt%, no more than 3.3 wt%, no more than 3 wt%, no more than 2.8 wt%, no more than 2.5 wt%, and no more than 2.3 wt% La2O3. In any exemplary embodiment, the glass composition may include greater than 1 wt% to less than 4 wt%, including between 1.4 wt% and 3.5 wt%, between 1.6 wt% and 3 wt%, and between 1.8 wt% and 2.7 wt%, including all endpoints and ranges therebetween.

[0026] The above-mentioned synergistic blends that comprise Y2O3 and La2O3 are conducive to reducing the overall concentration of CaO and MgO, thereby the demand for raw material limestone, dolomite and magnesite is lower, and these raw materials are just the contributors of glass batch carbon dioxide.Based on this, the total concentration of CaO and MgO in the glass composition should be no more than 18 % by weight, such as, for example, no more than 17.5 % by weight, no more than 17.2 % by weight, no more than 17 % by weight, no more than 16.8 % by weight, no more than 16.5 % by weight, no more than 16.2 % by weight and no more than 16 % by weight.In any exemplary embodiment, the glass composition may comprise CaO and MgO.

[0027] The glass composition may also advantageously include at least 9 wt % and no greater than 13 wt % MgO. In some exemplary embodiments, the glass composition includes at least 9.2 wt % MgO, including, for example, at least 9.5 wt %, at least 9.8 wt %, at least 10 wt %, at least 10.2 wt %, and at least 10.5 wt % MgO. Likewise, in any exemplary embodiment, the glass composition may include a MgO concentration of less than 13 wt %, including no greater than 12.8 wt %, no greater than 12.6 wt %, no greater than 12.4 wt %, no greater than 12.2 wt %, no greater than 12.0 wt %, no greater than 11.8 wt %, and no greater than 11.5 wt %. In any exemplary embodiment, the glass composition may include a MgO concentration of between 9 wt % and less than 13.0 wt %, or between 9.3 wt % and 12.8 wt %, or between 9.5 wt % and 12.5 wt %, or between 9.8 wt % and 12.2 wt %, including any endpoints and subranges therebetween.

[0028] As described above, the glass composition includes a lower concentration of CaO than conventional compositions, which reduces carbon emissions during manufacturing while also improving the elastic modulus of the formed fiber. Thus, the glass composition may include no more than 6 wt % CaO, and in some cases, no more than 5.5 wt % CaO. In any exemplary embodiment, the glass composition may include a CaO concentration of no more than 5.2 wt %, including, for example, no more than 5 wt %, no more than 4.8 wt %, and no more than 4.7 wt % CaO. Likewise, any of the exemplary embodiments may include a minimum of 3 wt %, such as, for example, a minimum of 3.2 wt %, 3.5 wt %, 3.7 wt %, 3.9 wt %, and 4.1 wt % CaO. In any exemplary embodiment, the glass composition may include between 3 wt % and 6.0 wt %, including between 3.5 wt % and 5.8 wt %, between 3.8 wt % and 5.5 wt %, between 4 wt % and 5.2 wt %, and between 4.1 wt % and less than 5.0 wt % CaO.

[0029] The total concentration of MgO and CaO is such that the ratio of SiO2 to the combined concentration of MgO and CaO (R2 = SiO2 / (CaO + MgO)) can be specifically tailored to be between 3.1 and 3.75, including between 3.2 and 3.6, and between 3.3 and 3.55, including all endpoints and subranges therebetween. SiO2 is the main oxide that forms the glass framework (O-Si-O bonds, 4 oxygens on each silicon and 2 silicons on each oxygen), and the alkaline earth metal oxides CaO and MgO provide Ca to the structure. 2+ and Mg 2+cations, each of which creates two non-oxygen bridges (NBO) in the glass former bond. A SiO2 / (CaO+MgO) ratio above 3.75 indicates that there are too many oxygen bridges in the structure, which may cause increased viscosity and difficulty in forming due to the high temperatures required for forming viscosity. A SiO2 / (CaO+MgO) ratio below 3.1 has too many NBOs, causing the glass structure to be brittle or loose, resulting in low viscosity along with low strength and low modulus. It has been found that a balanced value of the SiO2 / (CaO+MgO) ratio can be achieved to meet the needs of forming and market applications.

[0030] The glass composition also includes at least 50 wt % and less than 58 wt % SiO2. In some exemplary embodiments, the glass composition includes at least 51 wt %, including at least 52 wt %, at least 52.5 wt %, at least 53 wt %, at least 53.5 wt %, at least 53.8 wt %, at least 54 wt %, and at least 54.15 wt % SiO2. In some exemplary embodiments, the glass composition includes no more than 60 wt %, including no more than 58 wt %, no more than 57.5 wt %, no more than 57 wt %, no more than 56.5 wt %, no more than 56 wt %, and no more than 55.5 wt % SiO2. In some exemplary embodiments, the glass composition includes greater than 50 wt % to less than 58 wt %, greater than 52 wt % to less than 57 wt %, greater than 53 wt % to less than 56.5 wt %, or between 53.2 wt % and 55.8 wt %, including any endpoints and subranges therebetween.

[0031] In order to achieve both the desired mechanical properties and fiber forming process performance, an important aspect of the glass composition is to have an Al2O3 concentration of at least 18 wt% and no greater than 23 wt%. The inclusion of an Al2O3 concentration greater than 18 wt%, and particularly at least 18.5 wt%, generally ensures that the glass fibers formed from the composition will achieve a sufficient elastic modulus, as will be described in more detail below. The inclusion of greater than 23 wt% Al2O3 generally results in an increase in the glass liquidus to a level above the fiber forming temperature, which results in a negative ΔT.

[0032] In any exemplary embodiment, the glass composition may include at least 18.8 wt%, including at least 19 wt%, at least 19.3 wt%, at least 19.5 wt%, at least 19.7 wt%, at least 19.8 wt%, and at least 20 wt% Al2O3. In some exemplary embodiments, the glass composition includes not more than 22.8 wt%, including not more than 22.5 wt%, not more than 22 wt%, not more than 21.7 wt%, not more than 21.5 wt%, not more than 21.3 wt%, and not more than 21 wt% Al2O3. In some exemplary embodiments, the glass composition includes between 18.6 wt% and 22 wt% Al2O3, including between 18.9 wt% and 21.5 wt%, and between greater than 19 wt% and less than 21 wt%, including any endpoints and subranges therebetween.

[0033] In any exemplary embodiment, SiO2 and Al2O3 are present in a ratio R3 (R3 = SiO2 / Al2O3) that is specifically tailored to be between 2.5 and 3.0, including between 2.6 and 2.95, and between 2.7 and 2.9, including all endpoints and subranges therebetween. As previously described, SiO2 is the primary glass former. However, Al2O3 is also a glass former and serves to enhance the degree of connectivity in the glass structure. Therefore, there must be enough Al2O3 to enhance the connectivity of the glass network structure, but not so much that the crystallization of the network becomes too extensive, thereby maintaining a low liquidus temperature. A ratio of 2.7 to 2.9 has been found to be particularly advantageous for improving the modulus while maintaining an acceptable liquidus temperature.

[0034] The glass composition may also include at least 1 wt % of alkali metal oxides Li2O, Na2O, and K2O (collectively referred to as "R2O"), while maintaining the total R2O concentration below 3 wt %. In particular, Li2O is a special alkali metal oxide because it adds the desired Li that produces an NBO in the glass structure. + cations, thereby reducing melt and forming viscosities. The glass structure also has a high electric field strength (or low ionic radius), which allows the glass structure to be topologically closer together (densely packed), which stiffens the entire network. By effectively reducing or removing Na2O and K2O using higher quality raw materials, the amount of Li2O can be increased to increase the modulus while preventing the viscosity from becoming too close to the liquidus temperature.

[0035] The glass composition may include an amount of at least greater than 0.8 wt%, including, for example, at least 0.85 wt%, at least 0.95 wt%, at least 1.05 wt%, at least 1.15 wt%, at least 1.25 wt%, at least 1.4 wt%, and at least 1.5 wt% Li2O. Likewise, the glass composition includes less than 3 wt%, including, for example, not greater than 2.8 wt%, not greater than 2.5 wt%, not greater than 2.3 wt%, not greater than 2 wt%, not greater than 1.8 wt%, and not greater than 1.6 wt% Li2O. In any exemplary embodiment, the glass composition may include greater than 0.9 wt% to 2.5 wt%, including between 1.1 wt% and 2.1 wt%, between 1.3 wt% and 1.9 wt%, and between 1.4 wt% and 1.7 wt%, including all endpoints and ranges therebetween.

[0036] In some embodiments, the glass composition may be free or substantially free of Li2O and / or alkali metal oxides. As used herein, "substantially free" indicates an amount less than 1 wt%, such as less than 0.75 wt%, less than 0.5 wt%, less than 0.25 wt%, less than 0.1 wt%, less than 0.05 wt%, or less than 0.025 wt%. Thus, in some exemplary embodiments, the glass composition comprises less than 0.75 wt% Li2O, including less than 0.5 wt%, less than 0.3 wt%, less than 0.15 wt%, less than 0.075 wt%, and less than 0.05 wt% Li2O.

[0037] The glass composition may include at least 0.01 wt % Na2O and / or KO in individual or total amounts. In some exemplary embodiments, the glass composition includes 0 wt % to 1.0 wt %, including 0.01 wt % to 0.5 wt %, 0.03 wt % to 0.4 wt %, and 0.06 wt % to 0.3 wt %, including all endpoints and ranges therebetween of Na2O. In any exemplary embodiment, the glass composition may also include 0 wt % to 1 wt %, including 0.01 wt % to 0.5 wt %, 0.03 wt % to 0.3 wt %, and 0.04 wt % to 0.15 wt %, including all endpoints and ranges therebetween of KO. In any exemplary embodiment, the glass composition may be free of Na2O and / or KO.

[0038] The glass composition may also include TiO2 and / or Fe2O3 in an individual or combined amount of at least 0.01 wt%. For example, in any exemplary embodiment, the glass composition may optionally include 0 wt% to 1.5 wt%, including 0.01 wt% to 1 wt%, and 0.1 to 0.6 wt% TiO2. The glass composition may also optionally include up to 1 wt% Fe2O3. In some exemplary embodiments, the glass composition includes 0 wt% to 0.8 wt%, including 0.01 wt% to 0.6 wt%, and 0.1 wt% to 0.35 wt%, including all endpoints and ranges therebetween.

[0039] The glass composition may also include impurities and / or trace materials, but will not bring adverse effects to glass or glass fiber. These impurities may enter the glass as raw material impurities, or may be products formed by chemical reactions of molten glass and furnace components. Non-limiting examples of trace substances include, for example, strontium (SrO), barium (BaO), and combinations thereof. Trace substances may exist in the form of their oxides and may also include fluorine and / or chlorine. In some exemplary embodiments, the glass composition of the present invention includes not more than 2 weight %, including, for example, less than 1 weight %, less than 0.5 weight %, less than 0.2 weight %, less than 0.1 weight % and less than 0.05 weight % of BaO, SrO, P2O5, ZrO2, ZnO and SO3 each. In any exemplary embodiment, the glass composition may not include one or more of these compositions. Therefore, in any exemplary embodiment, the glass composition does not contain any one or more of BaO, SrO, P2O5, ZrO2, ZnO and SO3.

[0040] The glass composition may be free or substantially free of B2O3, although small amounts of B2O3 may be added to adjust fiber formation and finished glass fiber properties and may not adversely affect the final glass fiber properties if the content is less than a few percent. Thus, in any exemplary embodiment, the glass composition contains less than 1 wt% B2O3, including less than 0.75 wt%, less than 0.5 wt%, less than 0.3 wt%, less than 0.15 wt%, less than 0.075 wt%, and less than 0.05 wt% B2O3.

[0041] The glass composition may further include fluorine (F) in an amount of no greater than 1.0 wt %. For example, in any exemplary embodiment, the glass composition may optionally include 0 wt % to 0.9 wt %, including 0.01 wt % to 0.75 wt % and 0.05 wt % to 0.5 wt %, including all endpoints and ranges therebetween.

[0042] As used herein, the terms "weight percent," "weight %," "wt. %," and "percent by weight" are used interchangeably and are intended to mean the weight percent based on the total composition.

[0043] Table 1 below provides various exemplary composition ranges formulated according to the present inventive concepts.

[0044] Table 1

[0045] Exemplary Range A Exemplary Range B Exemplary Range C <![CDATA[SiO2]]> 50-58 52-56 53-55 <![CDATA[Al2O3]]> 18-23 18.5-22 19-21 CaO 3-6 3.5-5.5 4-5 MgO 9-13 9.5-12.5 10-11.5 <![CDATA[SiO2 / (MgO+CaO)]]> 3.1-3.7 3.2-3.68 3.3-3.55 <![CDATA[Y2O3]]> 4-7.5 5-7 5.5-6.5 <![CDATA[La2O3]]> 0.5-3 1-2.5 1.3-2.2 <![CDATA[Y2O3+La2O3]]> 5-10 6.5-9 7.5-8.5 <![CDATA[Na2O+K2O]]> 0-1 0.01-0.5 0.05-0.1 <![CDATA[Li2O]]> 0-2 0.95-1.8 1.2-1.65 <![CDATA[Fe2O3]]> 0-0.5 0.07-0.3 0.09-0.25 F 0-1 0.01-0.75 0.05-0.5 <![CDATA[TiO2]]> 0-0.6 0.01-0.5 0.03-0.3

[0046] As described above, the glass compositions of the present invention unexpectedly exhibit optimized elastic moduli while maintaining desirable forming properties, including fiber forming temperatures below 1,300°C, liquidus temperatures below 1,250°C (or in some exemplary embodiments, below 1,200°C), and positive ΔT values ​​of preferably at least 10°C.

[0047] Fiber tensile strength is also referred to herein simply as "strength". In some exemplary embodiments, the tensile strength of virgin fibers (i.e., unsized and unaffected laboratory-produced fibers) is measured using an Instron tensile testing device according to ASTM D2343-09. Exemplary glass fibers formed from the inventive glass compositions disclosed herein may have a fiber tensile strength of at least 4,400 MPa, including at least 4,450 MPa, at least 4,500 MPa, at least 4,530 MPa, at least 4,550 MPa, at least 4,570 MPa, at least 4,590 MPa, at least 4,600 MPa, at least 4,630 MPa, and at least 4,650 MPa. In some exemplary embodiments, glass fibers formed from the glass compositions of the present invention have a fiber tensile strength of 4,450 MPa to 4,900 MPa, including 4500 MPa to 4,800 MPa, 4,550 MPa to 4,750 MPa, including all endpoints and ranges therebetween.

[0048] The elastic modulus of glass fibers can be determined in various ways. In some exemplary embodiments, the elastic modulus is determined by a sonic wave technique that provides a sonic wave fiber elastic modulus by averaging measurements of five single glass fibers, the measurements being made according to the sonic wave measurement procedure outlined in the report "Glass Fiber Drawing and Measuring Facilities at the US Naval Ordnance Laboratory", Report No. NOLTR 65-87, June 23, 1965. The elastic modulus can also be determined as a bulk modulus, which is performed according to ASTM C1259.

[0049] Exemplary glass fibers formed from the glass compositions of the present invention may have a sonic fiber elastic modulus of at least 93 GPa, including at least 93.5 GPa, at least 94.0 GPa, at least 94.5 GPa, at least 95 GPa, at least 95.3 GPa, at least 95.5 GPa, at least 95.8 GPa, or at least 96 GPa. In any exemplary embodiment, exemplary glass fibers formed from the glass compositions of the present invention may have an elastic modulus between 93.5 GPa and 120 GPa, including between 94 GPa and 105 GPa, and between 95 GPa and 100 GPa, including all endpoints and ranges therebetween.

[0050] In any exemplary embodiment, the glass composition disclosed herein forms glass fibers having a density between 2.2 g / cc and 3.0 g / cc. Density can be measured on unannealed bulk glass by any method known and generally accepted in the art, such as the Archimedean method (ASTM C693-93 (2008)). In any exemplary embodiment, the glass fibers can have a density between 2.3 g / cc and 2.85 g / cc, including 2.5 g / cc to 2.8 g / cc, 2.55 g / cc to 2.75 g / cc, and 2.6 g / cc to 2.7 g / cc.

[0051] Density and elastic modulus determine the specific modulus. It is desirable to have a high specific modulus in order to obtain a lightweight composite material, thereby adding stiffness to the final product. Specific modulus is important in applications where the stiffness of the product is an important parameter, such as in wind energy and aerospace. As used herein, specific modulus is calculated by the following formula:

[0052] Specific modulus (MJ / kg) = acoustic fiber elastic modulus (GPa) / density (kg / cubic meter)

[0053] Exemplary glass fibers formed from the glass compositions of the present invention have a specific modulus of 33 MJ / kg to 40 MJ / kg, including 34 MJ / kg to 37 MJ / kg and 34.5 MJ / kg to 36 MJ / kg. In any exemplary embodiment, the glass fibers may have a specific modulus between 34.6 MJ / kg and 35 MJ / kg.

[0054] According to some exemplary embodiments, a method for preparing glass fibers from the above-mentioned glass composition is provided. Glass fibers can be formed by any means known in the art and conventionally used. In some exemplary embodiments, glass fibers are formed by obtaining raw material components and mixing the components in appropriate amounts to obtain the desired weight percentage of the final composition. The method may also include providing the glass composition of the present invention in molten form, and drawing the molten composition through the orifice in the bushing to form glass fibers.

[0055] The components of the glass composition can be obtained from suitable ingredients or raw materials, including but not limited to sand or pyrophyllite for SiO2, limestone, quicklime, wollastonite or dolomite for CaO, kaolin, alumina or pyrophyllite for Al2O3, dolomite, dolomitic quicklime, brucite, enstatite, talc, burnt magnesite or magnesite for MgO, and sodium carbonate, albite or sodium sulfate for Na2O. In some exemplary embodiments, glass fragments can be used to provide one or more of the desired oxides. As described above, the subject glass composition comprises reduced amounts of limestone, dolomite and magnesite.

[0056] Then the compound can be melted in a furnace or a melter, and the melted glass liquid enters the passage, and by being installed in the bushing below the passage, the glass fiber monofilament is formed by drawing. In some exemplary embodiments, the furnace or the melter is a traditional refractory furnace. By utilizing the refractory groove formed by refractory bricks, the manufacturing cost associated with the production of the glass fiber produced by the present composition can be reduced. In some exemplary embodiments, the bushing is a bushing based on a platinum alloy. Then the glass fiber precursor can be formed by bringing the single filament together. The fiber precursor can be wound and further processed in a conventional manner suitable for the intended application.

[0057] The operating temperature of the kiln, passage and bushing can be selected to properly adjust the viscosity of the glass, and can be maintained using a suitable method, such as a control device. The temperature at the front end of the melter can be automatically controlled to reduce or eliminate crystallization. The molten glass can then be pulled (drawn) through the holes or orifices in the bottom plate or end plate of the bushing to form glass fibers. According to some exemplary embodiments, the molten glass flow flowing through the bushing orifice is thinned into filaments by winding the precursor formed by a plurality of individual filaments on a forming tube mounted on a rotatable chuck of a winding machine or cutting it at a suitable speed. The glass fiber of the present invention can be obtained by any of the methods described herein or any known method for forming glass fibers.

[0058] The fibers can be further processed in a conventional manner suitable for the intended application. For example, in some exemplary embodiments, the glass fibers are sized with a sizing agent known to those skilled in the art. The sizing agent is not subject to any restrictions and can be any sizing agent suitable for application to the glass fibers. The sized fibers can be used to reinforce substrates, such as various plastics where the end use of the product requires high strength and stiffness and low weight. Such applications include, but are not limited to, non-woven felts and fabrics for the manufacture of wind turbine blades; infrastructure, such as reinforced concrete, bridges, etc.; and aerospace structures. Exemplary fabrics include, for example, unidirectional, uniaxial, multiaxial stitched fabrics, etc.

[0059] In this regard, some exemplary embodiments of the present invention include a composite material that combines the glass fiber of the present invention as described above with a combination of a hardenable matrix material. This may also be referred to as a reinforced composite product in this article. The matrix material can be any suitable thermoplastic or thermosetting resin known to those skilled in the art, such as but not limited to thermoplastic resins such as polyester, polypropylene, polyamide, polyethylene terephthalate and polybutylene, and thermosetting resins such as epoxy resins, unsaturated polyesters, phenolic resins, vinyl esters and elastomers. These resins can be used alone or in combination. Reinforced composite products can be used for wind turbine blades, steel bars, pipelines, fiber winding, muffler filling, sound absorption, etc.

[0060] According to another exemplary embodiment, the present invention provides a method for preparing a composite product as described above. The method may include combining at least one polymer matrix material with a plurality of glass fibers. Both the polymer matrix material and the glass fibers may be as described above.

[0061] Example

[0062] Exemplary glass compositions according to the present invention are prepared by mixing batch components in proportioned amounts to obtain final glass compositions having the oxide weight percentages shown in Tables 2, 3, and 4 below.

[0063] The raw materials were melted in a platinum crucible in an electrically heated furnace at a temperature of 1,600° C. for 3 hours. The forming temperature was measured using the rotating cylinder method described in ASTM C965-96 (2007), entitled “Standard Practice for Measuring Viscosity of Glass Above the Softening Point”, the contents of which are incorporated herein by reference. The liquidus temperature was measured by placing the glass in a platinum alloy boat with a certain temperature gradient for 16 hours, as defined in ASTM C829-81 (2005), entitled “Standard Practices for Measurement of Liquidus Temperature of Glass”, the contents of which are incorporated herein by reference. Density is measured by the Archimedean method as detailed in ASTM C693-93 (2008), entitled "Standard Test Method for Density of Glass Buoyancy," the contents of which are incorporated herein by reference.

[0064] The elastic modulus is measured by the sonic fiber technique according to the measurement procedure outlined in the report "Glass Fiber Drawing and Measuring Facilities at the US Naval Ordnance Laboratory", Report No. NOLTR 65-87, June 23, 1965. The specific modulus is calculated by dividing the measured elastic modulus (in GPa) by the density (in kg / m 3 as units) to calculate.

[0065] Strength was measured on virgin fibers using an Instron tensile testing device in accordance with ASTM D2343-09, entitled "Standard Test Method for Tensile Properties of Glass Fiber Strands, Yarns, and Rovings Used in Reinforced Plastics," the contents of which are incorporated herein by reference.

[0066] Table 2

[0067]

[0068]

[0069] Table 3

[0070]

[0071] Table 4

[0072]

[0073]

[0074] Tables 2, 3, and 4 show that the subject glass compositions overcome challenges to achieve a glass having a particular balance of forming properties (i.e., a fiber forming temperature below 1,300°C, a liquidus temperature no greater than 1,250°C (preferably no greater than 1,200°C), and a positive ΔT (preferably a ΔT of at least 10°C), and having an improved acoustic fiber elastic modulus of at least 94.5 GPa over prior art high performance glasses (comparative examples). Comparative prior art glass compositions were unable to achieve each of these parameters in a single glass composition, and thus the significant technical effects of the particular glass compositions described herein have been identified. As discussed above, even an apparently small increase in the fiber elastic modulus can have a large impact on the properties of a composite product formed therefrom due to the multiple increase in the overall fiber weight fraction of the product.

[0075] Specifically, as shown in Table 2, Comparative Examples 1, 2, and 4 each fall outside of at least two desired parameters (i.e., high silica, low alumina, low lanthanum, and low lithium (Comparative Example 1 only), and fail to achieve an elastic modulus of at least 94.5 GPa. Comparative Examples 3 and 4 include SiO2 / (MgO+CaO) concentrations above 3.75, and this difference results in a negative ΔT in Comparative Example 3 and a low elastic modulus in Comparative Example 4. In Table 3, Comparative Examples 6 and 8 exhibit low elastic moduli, and both comparative glass compositions include, among other differences, Y2 outside of the desired ratios of 2.0 and 4.0. O3 / La2O3 ratio. Comparative Examples 7 and 8 each include SiO2 / (MgO+CaO) ratios outside the desired ratio of 3.1 to 3.75, resulting in negative ΔT values, which are unacceptable for processing. In contrast, each of Examples 1 to 16 falls within the specific requirements and relationships described herein and produces glass compositions having fiber forming temperatures below 1,300°C, liquidus temperatures no greater than 1,250°C, and positive ΔT values ​​(preferably at least 10°C), while also producing glass fibers having sonic fiber elastic modulus values ​​of at least 94.5 GPa.

[0076] 1. A glass composition comprising: SiO2 in an amount of 50.0 wt% to 58.0 wt%; Al2O3 in an amount of 18.0 wt% to 23.0 wt%; CaO and MgO in an amount of less than 18.0 wt%; at least 5.0 wt% of Y2O3 and La2O3, wherein Y2O3 and La2O3 are present in a ratio R1 between 2.0 and 4.0 (R1=Y2O3 / La2O3); Li2O in an amount greater than 1.0 wt% to 2.0 wt%; and Li2O in an amount of 0.0 wt% to 0.1 wt%. % Na2O; 0.0 wt% to 0.2 wt% K2O; and 0.0 wt% to 0.5 wt% TiO2, wherein the glass composition has a ratio R2 (R2=SiO2 / (MgO+CaO)) between 3.1 and 3.75, wherein the glass composition has a fiber forming temperature of less than 1,300°C, a liquidus temperature of no greater than 1,250°C, and a ΔT of at least 10°C, and wherein a glass fiber formed from the glass composition has an acoustic fiber elastic modulus of at least 94.5 GPa.

[0077] Paragraph 2. A glass composition according to Paragraph 1, wherein the composition comprises 4.0 wt % to 8.0 wt % Y2O3 and 0.5 wt % to 4.0 wt % La2O3.

[0078] Paragraph 3. The glass composition of any of paragraphs 1 and 2, wherein the composition comprises no greater than 17.0 wt % CaO and MgO.

[0079] Paragraph 4. An energy-saving high-performance glass composition according to any one of paragraphs 1 to 3, wherein the composition comprises 18.3 wt % to 21.5 wt % Al 2 O 3 .

[0080] Paragraph 5. The glass composition of any one of paragraphs 1 to 4, wherein the composition is substantially free of B2O3.

[0081] Paragraph 6. The glass composition of any of paragraphs 1 to 5, wherein the composition comprises 1.25 wt % to less than 2.0 wt % Li2O.

[0082] Paragraph 7. The glass composition of any of paragraphs 1 to 6, wherein the composition has a fiber forming temperature of less than 1,270°C.

[0083] Paragraph 8. The glass composition of any of paragraphs 1 to 7, wherein the composition has a fiber forming temperature of less than 1,250°C.

[0084] Paragraph 9. A glass composition according to any one of paragraphs 1 to 8, wherein the composition has a ratio R3 (R3=SiO2 / Al2O3) between 2.5 and 3.0.

[0085] Paragraph 10. The glass composition of any of paragraphs 1 to 9, wherein the composition has a ratio R1 between 2.8 and 3.1.

[0086] Paragraph 11. The glass composition of any one of claims 1 to 10, wherein the composition further comprises up to 1.0 wt. % fluorine.

[0087] 12. A glass fiber formed from a glass composition, the glass composition comprising: SiO2 in an amount of 50.0 wt% to 56.0 wt%; Al2O3 in an amount of 18.0 wt% to 23.0 wt%; less than 18.0 wt% of CaO and MgO; Y2O3 in an amount of 4.5 wt% to 8.0 wt%; La2O3 in an amount of 0.5 wt% to 4.0 wt%; wherein Y2O3 and La2O3 are in a ratio between 2.0 and 4.0 R1 (R1 = Y2O3 / La2O3) is present; Na2O+K2O in an amount of 0.0 wt% to 0.5 wt%; TiO2 in an amount of 0.0 wt% to 0.5 wt%, wherein the glass composition has a ratio R2 (R2 = SiO2 / (MgO+CaO)) between 3.1 and 3.75, wherein the glass fiber has a density between 2.55 g / cc to 2.8 g / cc and an acoustic fiber elastic modulus of at least 94.5 GPa.

[0088] Paragraph 13. The glass fiber of paragraph 12, wherein the glass composition comprises 18.5 wt % to 21.5 wt % Al2O3.

[0089] Paragraph 14. The glass fiber according to any one of paragraphs 12 to 13, wherein the glass composition has a ratio R3 (R3=SiO2 / Al2O3) between 2.5 and 3.0.

[0090] Paragraph 15. The glass fiber of any of paragraphs 12 to 14, wherein the composition comprises 0.5 wt % to 2.0 wt % Li2O.

[0091] Paragraph 16. The glass fiber of any of paragraphs 12 to 15, wherein the composition comprises a total amount of Y2O3 and La2O3 greater than 7.0 wt%.

[0092] Paragraph 17. A method of forming continuous glass fibers, the method comprising: providing a molten composition according to any one of paragraphs 1 to 11; and drawing the molten composition through a bushing into continuous glass fibers.

[0093] 18. A reinforced composite product comprising a polymer matrix; and a plurality of glass fibers formed from a glass composition. The glass composition comprises SiO2 in an amount of 50.0 wt% to 58.0 wt%; Al2O3 in an amount of 18.0 wt% to 23.0 wt%; less than 18.0 wt% of CaO and MgO; at least 5.0 wt% of Y2O3 and La2O3, wherein Y2O3 and La2O3 are present in a ratio R1 between 2.0 and 4.0 (R1 = Y2O3 / La2O3); Li2O in an amount greater than 1.0 wt% to 2.0 wt%; and 0.0 wt% to 0.1 wt% of the glass composition. % Na2O; KO in an amount of 0.0 wt% to 0.2 wt%; TiO2 in an amount of 0.0 wt% to 0.5 wt%, wherein the glass composition has a ratio R2 (R2=SiO2 / (MgO+CaO)) between 3.1 and 3.75, wherein the glass composition has a liquidus temperature of no greater than 1,250°C and a ΔT between 10°C and 60°C, and wherein a glass fiber formed from the glass composition has an acoustic fiber elastic modulus of at least 94.5 GPa.

[0094] Paragraph 19. The reinforced composite product of Paragraph 18, wherein the reinforced composite product is in the form of a wind turbine blade.

[0095] Paragraph 20. The reinforced composite product of any of paragraphs 18 and 19, wherein the composition comprises 4.0 wt % to 8.0 wt % Y2O3 and 0.5 wt % to 4.0 wt % La2O3.

[0096] Paragraph 21. The reinforced composite product of any one of claims 18 to 20, wherein the composition comprises no greater than 17.0 wt% CaO and MgO.

[0097] Paragraph 22. The reinforced composite product of any one of claims 18 to 21, wherein the composition comprises 18.3 wt% to 21.5 wt% Al2O3.

[0098] Paragraph 23. The reinforced composite product of any one of claims 18 to 22, wherein the composition comprises 1.25 wt % to less than 2.0 wt % Li2O.

[0099] Paragraph 24. The reinforced composite product of any of paragraphs 18 to 23, wherein the composition has a fiber forming temperature of less than 1,270°C.

[0100] Paragraph 25. A reinforced composite product according to any one of paragraphs 18 to 24, wherein the composition has a ratio R3 (R3=SiO2 / Al2O3) between 2.5 and 3.0.

[0101] Paragraph 26. The reinforced composite product according to any of paragraphs 18 to 25, wherein the composition has a ratio R1 between 2.8 and 3.1.

[0102] Paragraph 27. A glass composition comprising: SiO2 in an amount of 50.0 wt% to 58.0 wt%; Al2O3 in an amount of 18.0 wt% to 23.0 wt%; less than 18.0 wt% CaO and MgO; and at least 5.0 wt% Y2O3 and La2O3, wherein Y2O3 and La2O3 are present in a ratio (R1 = Y2O3 / La2O3) between 2.0 and 4.0; wherein the glass composition has a fiber forming temperature between 1,200°C and 1,300°C and a ΔT of at least 10°C, and wherein a glass fiber formed from the glass composition has an acoustic fiber elastic modulus of at least 94.5 GPa.

[0103] Paragraph 28. The glass composition according to Paragraph 27, wherein the glass composition has a ratio R2 (R2=SiO2 / (MgO+CaO)) between 3.1 and 3.75.

[0104] Paragraph 29. The high performance glass composition of paragraph 27 or paragraph 28, wherein the glass composition has a liquidus temperature between 1,150°C and 1,250°C.

[0105] Paragraph 30. The high performance glass composition of any of paragraphs 27 to 29, wherein the glass composition has a fiber forming temperature between 1,210°C and 1,260°C.

[0106] The invention of the present application has been described above generally and with reference to specific embodiments. Although the present invention has been described in what are believed to be preferred embodiments, multiple alternatives known to those skilled in the art may be selected from the general disclosure. The present invention is not otherwise limited except as described in the claims listed.

Claims

1. A glass composition, comprising: SiO2 in an amount of 50 wt % to 58 wt %; Al2O3 in an amount of 18 to 23 wt%; Less than 18 wt.% CaO and MgO; at least 5 wt.% of Y2O3 and La2O3, wherein Y2O3 and La2O3 are present in a ratio R1 between 2 and 4 (R1=Y2O3 / La2O3); an amount greater than 1 wt % to 2 wt % Li2O; Na2O in an amount of 0 wt% to 0.1 wt%; K2O in an amount of 0 wt% to 0.2 wt%; and TiO2 in an amount of 0 wt % to 0.5 wt %, wherein the glass composition has a ratio R2 (R2=SiO2 / (MgO+CaO)) between 3.1 and 3.75, wherein the glass composition has a fiber forming temperature of less than 1,300°C, a liquidus temperature of no greater than 1,250°C, and a ΔT of at least 10°C, and The glass fiber formed from the glass composition has a sonic fiber elastic modulus of at least 94.5 GPa.

2. The glass composition according to claim 1, wherein the composition comprises: 4 wt % to 8 wt % Y2O3; and 0.5 wt% to 4 wt% La2O3.

3. The glass composition of any one of claims 1 and 2, wherein the composition comprises no more than 17 wt. % CaO and MgO.

4. The glass composition according to any one of claims 1 to 3, wherein the composition comprises 18.3 wt. % to 21.5 wt. % Al2O3.

5. The glass composition according to any one of claims 1 to 4, wherein the composition is substantially free of B2O3.

6. The glass composition of any one of claims 1 to 5, wherein the composition comprises 1.25 wt% to less than 2 wt% Li2O.

7. The glass composition of any one of claims 1 to 6, wherein the composition has a fiber forming temperature of less than 1,270°C.

8. The glass composition of any one of claims 1 to 7, wherein the composition has a fiber forming temperature of less than 1,250°C.

9. The glass composition according to any one of claims 1 to 8, wherein the composition has a ratio R3 (R3 = SiO2 / Al2O3) between 2.5 and 3.

10. The glass composition according to any one of claims 1 to 9, wherein the composition has a ratio R1 between 2.8 and 3.

1.

11. The glass composition of any one of claims 1 to 10, wherein the composition further comprises up to 1 wt. % fluorine.

12. A glass fiber formed from a glass composition, the glass composition comprising: SiO2 in an amount of 50 wt % to 56 wt %; Al2O3 in an amount of 18 to 23 wt%; Less than 18.0 wt. % CaO and MgO; Y2O3 in an amount of 4.5 wt% to 8 wt%; La2O3 in an amount of 0.5 wt% to 4 wt%; wherein Y2O3 and La2O3 are present in a ratio R1 between 2 and 4 (R1 = Y2O3 / La2O3); Na2O+K2O in an amount of 0 wt% to 0.5 wt%; and TiO2 in an amount of 0 wt % to 0.5 wt %, wherein the glass composition has a ratio R2 (R2=SiO2 / (MgO+CaO)) between 3.1 and 3.75, The glass fibers have a density between 2.55 g / cc and 2.8 g / cc and an acoustic fiber elastic modulus of at least 94.5 GPa.

13. The glass fiber of claim 12, wherein the glass composition comprises 18.5 wt% to 21.5 wt% Al2O3.

14. Glass fiber according to any one of claims 12 to 13, wherein the glass composition has a ratio R3 (R3 = SiO2 / Al2O3) between 2.5 and 3.

15. The glass fiber of any one of claims 12 to 14, wherein the composition comprises 1 to 2 wt% Li2O.

16. The glass fiber of any one of claims 12 to 15, wherein the composition comprises a total amount of greater than 7 wt% Y2O3 and La2O3.

17. A method of forming continuous glass fibers, the method comprising: Providing a molten composition according to any one of claims 1 to 11; as well as The molten composition is drawn through an orifice into continuous glass fibers.

18. A reinforced composite material product, comprising: a polymer matrix; and A plurality of glass fibers formed from a glass composition comprising: SiO2 in an amount of 50 wt % to 58 wt %; Al2O3 in an amount of 18 to 23 wt%; Less than 18 wt.% CaO and MgO; At least 5 wt% of Y2O3 and La2O3, wherein the ratio of Y2O3 and La2O3 is between 2 and 4 (R1 = Y2O3 / La2O3) exist; an amount greater than 1 wt % to 2 wt % Li2O; Na2O in an amount of 0 wt% to 0.1 wt%; K2O in an amount of 0 wt% to 0.2 wt%; and TiO2 in an amount of 0 wt % to 0.5 wt %, The glass composition has a ratio R2 (R2= SiO2 / (MgO+CaO)), wherein the glass composition has a liquidus temperature of no greater than 1,250°C and a ΔT between 10°C and 60°C, and The glass fiber formed from the glass composition has a sonic fiber elastic modulus of at least 94.5 GPa.

19. The reinforced composite product of claim 18, wherein the reinforced composite product is in the form of a wind turbine blade.

20. The reinforced composite product according to any one of claims 18 and 19, wherein the composition comprises: 4 wt % to 8 wt % Y2O3; and 0.5 wt% to 4 wt% La2O3.

21. A reinforced composite product according to any one of claims 18 to 20, wherein the composition comprises no more than 17 wt% CaO and MgO.

22. A reinforced composite product according to any one of claims 18 to 21, wherein the composition comprises 18.3 to 21.5 wt% Al2O3.

23. A reinforced composite product according to any one of claims 18 to 22, wherein the composition comprises from 1.25 wt% to less than 2 wt% Li2O.

24. A reinforced composite product according to any one of claims 18 to 23, wherein the composition has a fiber forming temperature of less than 1,270°C.

25. A reinforced composite product according to any one of claims 18 to 24, wherein the composition has a ratio R3 (R3 = SiO2 / Al2O3) comprised between 2.5 and 3.

26. A reinforced composite product according to any one of claims 18 to 25, wherein the composition has a ratio R1 comprised between 2.8 and 3.

1.

27. A glass composition, comprising: SiO2 in an amount of 50 wt % to 58 wt %; Al2O3 in an amount of 18 to 23 wt%; Less than 18 wt% CaO and MgO; and at least 5 wt.% Y2O3 and La2O3, wherein Y2O3 and La2O3 are present in a ratio between 2 and 4 (R1 = Y2O3 / La2O3); wherein the glass composition has a fiber forming temperature between 1,200°C and 1,300°C and a ΔT of at least 10°C, and The glass fiber formed from the glass composition has a sonic fiber elastic modulus of at least 94.5 GPa.

28. The glass composition of claim 27, wherein the glass composition has a ratio R2 (R2 = SiO2 / (MgO+CaO)) between 3.1 and 3.

75.

29. The glass composition of claim 27 or claim 28, wherein the glass composition has a liquidus temperature between 1,150°C and 1,250°C.

30. The glass composition of any one of claims 27 to 29, wherein the glass composition has a fiber forming temperature between 1,210°C and 1,260°C.